2009
DOI: 10.1088/0953-4075/42/6/065401
|View full text |Cite
|
Sign up to set email alerts
|

The fifth-order nonlinearity of CS2

Abstract: Nonlinear refraction and absorption in carbon disulfide (CS2) has been investigated using the Z-scan technique with a femtosecond pulse laser at a wavelength of 800 nm in a broad intensity range. It is found that the origin of nonlinearity depends on the laser intensity. At low intensity, the nonlinearity is mainly due to the third-order process. The third- and fifth-order processes are at present simultaneously at high intensity. We also find the critical intensity value which determines whether the fifth-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Before dealing with the sample, the Z-scan experiment on CS 2 with a thickness of 1 mm was first performed for testing and calibration. Through measurement and calculation, the third-order nonlinear refractive index of CS 2 was evaluated to be 2.6 × 10 −19 m 2 ∕W, which was in good agreement with previous measurements at this range of pulse duration (2.5 × 10 −19 m 2 ∕W, 3 × 10 −19 m 2 ∕W) [19,20]. So it might be certain that the experiment setup was working normally.…”
Section: Methodssupporting
confidence: 86%
“…Before dealing with the sample, the Z-scan experiment on CS 2 with a thickness of 1 mm was first performed for testing and calibration. Through measurement and calculation, the third-order nonlinear refractive index of CS 2 was evaluated to be 2.6 × 10 −19 m 2 ∕W, which was in good agreement with previous measurements at this range of pulse duration (2.5 × 10 −19 m 2 ∕W, 3 × 10 −19 m 2 ∕W) [19,20]. So it might be certain that the experiment setup was working normally.…”
Section: Methodssupporting
confidence: 86%
“…Indeed, measurements performed at moderate intensities have provided the values n 4 = (1. 1.064 μm [15], in contrast to n 4 = −2 × 10 −35 m 4 /W 2 at 800 nm [19] or n 4 = −5.2 × 10 −35 m 4 /W 2 at 920 nm [10]. The change in the sign of n 4 with wavelength is related to the location of the third harmonic with respect to the absorption bands of the material.…”
Section: An Adapted Modelmentioning
confidence: 91%
“…However, Kong et al have reported an appreciable three-photon absorption γ at 800 nm [19]; they also found the value of γ = 1. 200 nm [10], which is approximately the third harmonic λ/3 of the wavelength λ = 532 nm.…”
Section: Nonlinear Index Measurementsmentioning
confidence: 96%
“…Indeed, measurements performed at moderate intensities have provided the values n 4 = (1.2 ± 0.3)×10 −32 m 4 /W 2 at λ = 532 nm, n 4 = (2.2 ± 0.4)×10 −33 m 4 /W 2 at λ = 1.064 µm [8], in contrast with n 4 = −2×10 −35 m 4 /W 2 at 800 nm [10], or n 4 = −5.2×10 −35 m 4 /W 2 at 920 nm [3]. The change in the sign of n 4 with wavelength is related to the location of the third harmonic with respect to the absorption bands of the material.…”
Section: Results and Conclusionmentioning
confidence: 98%